2010
DOI: 10.1074/jbc.r110.125294
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Non-structural Protein 3 (HCV NS3): A Multifunctional Antiviral Target

Abstract: Hepatitis C virus non-structural protein 3 contains a serine protease and an RNA helicase. Protease cleaves the genomeencoded polyprotein and inactivates cellular proteins required for innate immunity. Protease has emerged as an important target for the development of antiviral therapeutics, but drug resistance has turned out to be an obstacle in the clinic. Helicase is required for both genome replication and virus assembly. Mechanistic and structural studies of helicase have hurled this enzyme into a promine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
133
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(138 citation statements)
references
References 99 publications
(68 reference statements)
3
133
0
2
Order By: Relevance
“…Some acridones from Rutaceae plants showed great 153 antiviral activity against viruses with DNA genomes like herpes simplex virus serotypes 1 and 2 154 (HSV-1 and HSV-2), human cytomegalovirus (HCMV) and Epstein-Barr virus (Chansriniyom et 155 al., 2009;Itoigawa et al, 2003;Takemura et al, 1995;Yamamoto et al, 1989). For RNA 156 viruses, acridones presented activity against HIV-1, bovine viral diarrhea virus (BVDV), all 157 serotypes of dengue virus (DENV) and HCV, the last three belonging to the Flaviviridae family 158 (Fujiwara et al, 1999;Houe, 2003;Mazzucco et al, 2015;Raney et al, 2010;Sepulveda et al, 159 2008;Stankiewicz-Drogon et al, 2010;Stankiewicz-Drogon et al, 2008;Tabarrini et al, 2006;160 Turpin et al, 1998). 161 Our results showed that Fac4 inhibited up to 92% of HCV replication in the context of either the 162 subgenomic replicon or full length JFH1 HCVcc.…”
Section: Discussion 150mentioning
confidence: 99%
“…Some acridones from Rutaceae plants showed great 153 antiviral activity against viruses with DNA genomes like herpes simplex virus serotypes 1 and 2 154 (HSV-1 and HSV-2), human cytomegalovirus (HCMV) and Epstein-Barr virus (Chansriniyom et 155 al., 2009;Itoigawa et al, 2003;Takemura et al, 1995;Yamamoto et al, 1989). For RNA 156 viruses, acridones presented activity against HIV-1, bovine viral diarrhea virus (BVDV), all 157 serotypes of dengue virus (DENV) and HCV, the last three belonging to the Flaviviridae family 158 (Fujiwara et al, 1999;Houe, 2003;Mazzucco et al, 2015;Raney et al, 2010;Sepulveda et al, 159 2008;Stankiewicz-Drogon et al, 2010;Stankiewicz-Drogon et al, 2008;Tabarrini et al, 2006;160 Turpin et al, 1998). 161 Our results showed that Fac4 inhibited up to 92% of HCV replication in the context of either the 162 subgenomic replicon or full length JFH1 HCVcc.…”
Section: Discussion 150mentioning
confidence: 99%
“…Generations can be distinguished within the PI class based on binding properties with the catalytic triad of the NS3 protease (Salam and Akimitsu, 2013). The first-generation PIs are linear α-ketoamide compounds telaprevir and boceprevir, which covalently bind the enzyme and display only antiviral activity towards HCV genotype 1 (Raney et al, 2010). The second-generation PIs such as faldaprevir and simeprevir, bind the catalytic triad in a non-covalent manner, and show antiviral activity towards non-1 HCV genotypes too (De Luca et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…where Ser139, His57, and Asp81 in HCV NS3 form the catalytic triad of the enzyme ( Figure 2). The crystal structure and specificity of HCV protease have been characterized in detail [9][10][11]. Its catalytic triad has been found to be constituted of Ser139, His57, and Asp81 residues ( Figure 2).…”
mentioning
confidence: 99%